MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA PEMENTASAN DRAMA DENGAN MENGGUNAKAN METODE BERMAIN PERAN - Hasniyati Hasniyati; Novia Erwandi; Aida Fitri; Rizki Kurniawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to describe the learning outcomes of class XI MIA 1 SMA Negeri Modal Bangsa in staging drama through the role playing method. This type of research is descriptive research with a quantitative approach. Data collected by test and observation. Data analysis using simple statistical analysis. The results of the study show that the table above shows that the average score of students reaches 81.2 and the percentage of learning completeness reaches 92.5% or in other words around 37 out of 40 students complete learning. The highest score is 95 and the lowest score is 65. These results indicate that learning completeness has increased better than learning with conventional methods. The implementation of this research has met the target of minimum completeness criteria. Thus, the conclusion of this study is that the learning outcomes of class XI MIA 1 SMA Negeri Modal Bangsa have increased by using the role playing method